Babesia bigemina: Identification of B cell epitopes associated with parasitized erythrocytes - Vidotto, Odilon; McElwain, Terry F.; Machado, Rosangela Z. [UNESP]; Perryman, Lance E.; Suarez, Carlos E.; Palmer, Guy H. (Elsevier, 1995)
Rhoptries are involved in host cell invasion and rhoptry polypeptides, including the Babesia bigemina rhoptry-associated protein-1 (RAP-1), are targets for protective immune responses. Polyclonal antisera produced against isolated rhoptries is directed predominantly against RAP-1 and reacts with both the merozoite and the membrane of parasitized erythrocytes. To determine whether these B cell epitopes associated with the parasitized erythrocyte are derived from RAP-1 or, alternatively, from previously undetected merozoite polypeptides, monoclonal antibodies (mAbs) were generated from mice immunized with rhoptries isolated from the JG-29 clone of the Mexico strain. The anti-RAP-1 mAbs bound only merozoites in a punctate immunofluorescence pattern. A second group of four mAbs, none of which were reactive with RAP-1, bound the parasitized erythrocyte. Two of these latter mAbs, 64/44.17.3 and 64/05.7.2, reacted only with parasitized erythrocytes that had been permeabilized. MAb 64/44.17.3 bound a 54-kDa merozoite polypeptide while 64/05.7.2 bound a ≥225-kDa merozoite polypeptide. MAbs 64/32.8.5 and 64/38.5.3 recognized epitopes on 17.5- and 76-kDa polypeptides exposed on the external surface of intact parasitized erythrocytes. The results indicate that the identified RAP-1 epitopes are not associated with the erythrocyte cytoskeleton or membrane and that anti-RAP-1 immunity is most likely generated against the free merozoite. All new mAbs reacted with every B. bigemina strain tested (Mexico, Puerto Rico, St. Croix, Texcoco, Jaboticabal). The conservation of RAP-1 epitopes among these strains supports the continued testing of RAP-1 as a vaccine component. In addition, the identification of epitopes expressed on the surface of erythrocytes infected with all five strains provides new candidate immunogens. © 1995 Academic Press, Inc.